2022
DOI: 10.1590/1519-6984.245368
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enteroparasites in foliar vegetables commercialized in street- and supermarkets in Aparecida de Goiânia, Goiás, Brazil

Abstract: Foliar vegetables contaminated with fecal residues are an important route of transmission of intestinal parasites to humans. The aim of this study was to evaluate the presence of parasitic forms of protozoa and helminths on lettuces (Lactuca sativa) and collard greens (Brassica oleracea) sold in street- and supermarkets in the city of Aparecida de Goiânia, Goiás, Brazil. A total of 30 samples of each vegetable (15 samples from each supermarkets and street markets) was analyzed. All samples were processed by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…2 ; Addotopma;file: Table S1). Several studies have shown soil contamination with this cestode (0.1–26.3%) [ 22 31 ], as well as food contamination (1.7%) [ 32 ]. The wide geographical distribution of this parasite is unsurprising, as invertebrate intermediate hosts are also found throughout the world, with fleas being the most frequent ectoparasite of dogs and cats [ 5 , 21 , 33 ].…”
Section: Epidemiology Prevalence and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ; Addotopma;file: Table S1). Several studies have shown soil contamination with this cestode (0.1–26.3%) [ 22 31 ], as well as food contamination (1.7%) [ 32 ]. The wide geographical distribution of this parasite is unsurprising, as invertebrate intermediate hosts are also found throughout the world, with fleas being the most frequent ectoparasite of dogs and cats [ 5 , 21 , 33 ].…”
Section: Epidemiology Prevalence and Distributionmentioning
confidence: 99%
“…However, when there is no contact with animals, other means of transmission cannot be discarded, including the role of other ectoparasite vectors, such as the human flea ( P. irritans ) [ 9 ]; in addition, consideration must be given to immunosuppressive conditions or poor hygiene, both of which may facilitate infection [ 13 , 59 , 65 ]. The presence of proglottids or ovigerous capsules in soil or food [ 25 , 28 , 32 , 58 ], as well as co-habitation with other infected people or companion animals [ 60 ], only represents an indirect risk of infection as the life-cycle of D. caninum is heteroxenous, and the infective cysticercoid larvae are only present in the intermediate host [ 2 , 6 ].…”
Section: Dogs and Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, (Rocha et al, 2021) analyzed lettuce samples in the city of Goiânia, Brazil, and found 45% of contamination with helminths eggs, protozoan cysts and oocysts. The more frequent parasitic forms were eggs of Ancylostomatidae, Strongyloididae, Ascarididae and Taeniidae , or oocysts of Eimeriidae, Cystoisospora sp .…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal parasitic infections are a serious public health problem that globally affects more than a quarter of the world's population (Jourdan et al, 2018;Li et al, 2020;Rocha et al, 2021). In Brazil, a high prevalence of intestinal parasites is common, especially in regions of low socioeconomic status, and is closely linked to the lack of basic sanitation, inadequate personal hygiene and lack of care in food handling.…”
Section: Introductionmentioning
confidence: 99%